Meningkatkan Hasil Belajar Peserta Didik dengan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Kuis Interaktif pada Mata Pelajaran IPAS Kelas IV SD Negeri 44 Ampenan - Febbyola, Via; Busyairi, Ahmad; Andriyani, Novalia (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the IPAS learning outcomes of fourth-grade students at SD Negeri 44 Ampenan through the implementation of the Problem-Based Learning (PBL) model. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The participants consisted of 18 fourth-grade students at SD Negeri 44 Ampenan. The independent variable was the Problem-Based Learning model, while the dependent variable was students’ IPAS learning outcomes. Data were collected using test techniques, and data analysis was carried out using descriptive comparative analysis in the form of percentages of IPAS learning outcomes across the pre-cycle, Cycle I, and Cycle II stages. The results indicate that learning through the Problem-Based Learning model supported by interactive quizzes effectively improved students’ learning outcomes in the IPAS subject. Prior to the intervention, only 8 students (45%) achieved mastery in the pre-cycle. This number increased to 9 students (50%) in Cycle I and further rose to 15 students (84%) in Cycle II. The study concludes that the implementation was successful, as it met the performance indicator, with 84% of students achieving the minimum mastery criterion (KKM) of 70.